2000
DOI: 10.3164/jcbn.28.69
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Selenium on N-Nitrosodiethylamine and Phenobarbital-Promoted Rat Liver Carcinogenesis.

Abstract: SummaryThe chemoprotective efficacy of selenium, a dietary micronutrient, against chemically-induced hepatocarcinogenesis in rats was investigated. Carcinogenesis was performed by a single intraperitoneal injection of N-nitrosodiethylamine (DEN, 200 mg/kg body weight) with phenobarbital (0.05%) as a promoter in rats. When selenium-supplemented (4 ppm) drinking water was provided ad libitum throughout the experimental period, before the initiation, or during the promotion period it was found to be effective in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(19 reference statements)
1
9
0
Order By: Relevance
“…Studies show that high fat selenium deficiency results in an increase in foci development [50]. In our study, we also observed decreased selenium content in hepatoma rats [10]. Baldwin and Parker [51] cited that dietary selenium and fat might function by different mechanisms at different stages of carcinogens.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Studies show that high fat selenium deficiency results in an increase in foci development [50]. In our study, we also observed decreased selenium content in hepatoma rats [10]. Baldwin and Parker [51] cited that dietary selenium and fat might function by different mechanisms at different stages of carcinogens.…”
Section: Discussionsupporting
confidence: 64%
“…The results of our previous findings clearly indicate that in their particular two-stage model of hepatocarcinogenesis in rats, the supplementation with 4 ppm selenite during the entire period, before initiation, and/or during promotion greatly reduced the incidence, multiplicity, and size of visible persistent nodules [10] with a concurrent alteration in the lipid and lipid-metabolizing enzymes (present observations).…”
Section: Discussionmentioning
confidence: 53%
“…either before initiation or during initiation and/or during promotion can significantly reduce cancer incidence and morbidity. 12 At the same concentration it did not affect the control animals. 12 The purpose of the present study is to demonstrate the protective response of sodium selenite by modulating marker enzyme changes in rat hepatocarcinogenesis induced by N-nitrosodiethylamine.…”
Section: Introductionmentioning
confidence: 84%
“…12 At the same concentration it did not affect the control animals. 12 The purpose of the present study is to demonstrate the protective response of sodium selenite by modulating marker enzyme changes in rat hepatocarcinogenesis induced by N-nitrosodiethylamine. This may help us further to understand the additive inhibitory effect of sodium selenite on the biochemistry of DEN-induced rat liver carcinogenesis.…”
Section: Introductionmentioning
confidence: 84%
“…Previous studies from our laboratory had shown that an increased concentration of Se in different organs of tumour-bearing rats is not directly proportional to the chemopreventive effectiveness of this compound. 11 However the chemopreventive/chemotherapeutic effect of Se is not ruled out. A striking observation of the present study was that Se supplementation before initiation, selenite against hepatoma with reference to non-enzymic antioxidants 269 during initiation and during promotion stages, demonstrated a pronounced effect in inhibiting the appearance of hepatic nodules of more than 3 mm in size from 41.9% (group 2) to 12.7% (group 3), 23.4% (group 5) and 27.8% (group 7) respectively.…”
Section: Discussionmentioning
confidence: 99%